2021
DOI: 10.1002/ange.202110917
|View full text |Cite
|
Sign up to set email alerts
|

Stable Interface Chemistry and Multiple Ion Transport of Composite Electrolyte Contribute to Ultra‐long Cycling Solid‐State LiNi0.8Co0.1Mn0.1O2/Lithium Metal Batteries

Abstract: Severe interfacial side reactions of polymer electrolyte with LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811) cathode and Li metal anode restrict the cycling performance of solid-state NCM811/ Li batteries.H erein, we propose ac hemically stable ceramicpolymer-anchored solvent composite electrolyte with high ionic conductivity of 6.0 10 À4 Scm À1 ,w hiche nables the solid-state NCM811/Li batteries to cycle 1500 times.T he Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 nanowires (LNs) can tightly anchor the essential N, N-dimethylformamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…S2, ESI †), confirming the solid-state property of 1PVHF1FSI. 22,[26][27][28] On the other hand, trace DMF plays the beneficial roles in both the cathode and the anode such as changing the reaction pathway of SPAN and helping form a Li x N-containing SEI component with good ionic conductivity. Commonly, solid polymer electrolytes with good mechanical properties are beneficial for inhibiting lithium dendrite growth.…”
Section: Resultsmentioning
confidence: 99%
“…S2, ESI †), confirming the solid-state property of 1PVHF1FSI. 22,[26][27][28] On the other hand, trace DMF plays the beneficial roles in both the cathode and the anode such as changing the reaction pathway of SPAN and helping form a Li x N-containing SEI component with good ionic conductivity. Commonly, solid polymer electrolytes with good mechanical properties are beneficial for inhibiting lithium dendrite growth.…”
Section: Resultsmentioning
confidence: 99%
“…1−3 SSEs can greatly improve the safety and match the lithium metal anode, thus enhancing the energy densities of corresponding solid-state lithium batteries. 4,5 Among various SSEs, polymer electrolytes (such as poly-(ethylene oxide) (PEO), 6 polyvinylidene fluoride (PVDF), 7 poly(methyl methacrylate) (PMMA), 8 and polyacrylonitrile (PAN) 9 based electrolytes) with flexibility and thus good contact with electrodes and easily scalable production have presented promising industrial application prospects and compatibility with commercial lithium-ion batteries. However, lithium ions mainly transmit through the segmental movement of the amorphous domain in polymer electrolytes, resulting in a poor room-temperature ionic conductivity, which has been a decisive issue hindering their further application.…”
mentioning
confidence: 99%
“…24 Recently, 6 Li-tracer NMR spectroscopy was applied and presents great superiority to track the Li + transport pathways. Through cycling the 6 5 and PAN-5%LLZO nanowires 26 by utilizing a similar approach. Understanding of the decisive factor for the preferential ion transport pathway is still insufficient and thus crucially necessary for a rational design of the composite polymer electrolytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors have been identified that influence the compatibility of the cathode−electrolyte interface, such as increased active particle size, increased external stress during cycling, and temperature during battery assembly. 131 Swamy et al 132 exploited a b-Li 3 PS 4 /C composite as their electroactive electrode and found that the oxidation of S 2− in sulfide SEs at high voltage produced elemental sulfur. Zhang et al 133 performed in situ EIS and Raman spectroscopy studies to monitor the interface evolutions in the Li-Ni 0.8 Co 0.1 Mn 0.1 O 2 (NCM)/Li 6 PS 5 Cl/Li cell.…”
Section: Boosted the Ccd By Applying A T H I N C O A T I N G O Fmentioning
confidence: 99%